Predicting Covid-19 Vaccination Intention: The Role of Health Belief Model of Muslim Societies in Yogyakarta - Erawan, Muhammad Aufar Saputra Pratama; Zaid, Zaid; Pratondo, Katon; Lestari, Ahdiana Yuni (Al-Sihah: The Public Health Science Journal, 2021)
After implementing various policies to deal with covid-19, which were still considered ineffective, the Government of Indonesia is now trying to implement a mandatory vaccination policy for all of its citizens. However, the program's success depended on the perceptions and beliefs that developed in the community regarding the covid-19 vaccine itself. This study aimed to examine the Health Belief Model (HBM) effect using the variables of perceived susceptibility, severity, benefits, and barriers on covid-19 vaccination intention. By using a quantitative method that was cross-sectional and involving 452 respondents who were taken using the purposive sampling method. After being analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM), the results of this study showed that perceived susceptibility, severity, and benefits had a positive influence on covid-19 vaccination intention. At the same time, the perceived barrier showed a negative effect. In the end, this study provided a theoretical model of HBM in predicting behavioral intention, which in turn, predicted behavior. On the other hand, this research also provided a starting point for research into the interest in vaccination against covid-19 in Indonesia